PENGARUH KETEBALAN BATU KORAL PADA TANAH LEMPUNG DAN TANAH BERPASIR TERHADAP TEGANGAN LANGKAH DAN TEGANGAN SENTUH - I Putu Nova Suciawan; I Gusti Ngurah Janardana; I Wayan Arta Wijaya (Program Studi Teknik Elektro UNUD, 2021)
Ground fault currents that flow in the disturbance area and in the switchyard area of theSubstation create tension on the ground which can result in touch voltage and step voltage thatexceed the allowable limits of human safety. The thickness of the coral rock affects the value ofthe touch voltage and step voltage. This research was conducted to determine the effect of thethickness of the coral rock on clay and sandy soil on stepvvoltage anddtouchvvoltage.Themethod used is by measuring coral, clay soils and sandy soils, then calculating thevvalueofttouch voltageaand stepvvoltage based on the thickness of the coral used. The results ofcalculations and analysis of several thicknesses of coral stones used in clay soil, obtained theresults of the touch voltage in the dry state of 153.5615 volts and in the wet state of 152.0702volts, the results of the step voltage in the dry state 188.5057 volts and in the w et state 182 ,8265 volts. On sandy soil, the results of the touch voltage are 153.6893 volts in dry conditionand 152.1981 volts in wet conditions, the results of the step voltage in dry conditions are189.141 volts and in wet conditions 183.4349 volts.